Pengalaman Pensyarah dalam Proses Penyeliaan Pelajar Pascasiswazah Antarabangsa TVET China di UTHM: Satu Kajian Kualitatif - Baba, Farah Fatihah; Rohiat, Mohd Akmal (Research and Innovation in Technical and Vocational Education and Training, 2025)
This study aims to identify the unique challenges and opportunities faced by supervisors during the supervision process, as well as effective strategies and practices used to support students in achieving academic success. The internationalization of higher education has led to an increasingly diverse student population, creating new challenges for academic institutions. In Malaysia, while postgraduate supervision is a critical element of higher education, research on the supervision of international students in TVET remains limited. Therefore, understanding the experiences of supervisors overseeing postgraduate TVET students from China is crucial for bridging gaps in academic and cultural support. This study employs a case study design within a qualitative framework. Data were collected through semi-structured interviews with three supervisors from the Faculty of Technical and Vocational Education (FPTV) at UTHM, who supervise postgraduate TVET students from China. Content analysis was used to identify patterns and themes derived from the supervisors’ experiences and perceptions of the supervision process. The findings provide valuable insights into the supervision of international postgraduate TVET students from China, highlighting challenges such as cultural and language barriers, alongside opportunities for cross-cultural collaboration and mentorship. The study also proposes practical strategies to enhance the supervision process, including cultural competency training, improved communication practices, and tailored academic support systems. By addressing the unique dynamics of postgraduate TVET supervision, this study contributes to the discourse on the internationalization of higher education and offers recommendations to improve supervisory practices in Malaysian universities and beyond. In addition to identifying challenges and opportunities, this study also proposes several practical solutions such as providing language preparation programs for international students, cultural competency training for supervisors, and the use of flexible digital communication platforms. The implications of this study for higher education policy include the need to develop supervisory guidelines that are more inclusive, stable, and responsive to the needs of international students, particularly within the growing context of global TVET